1992
DOI: 10.1530/acta.0.1270023
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and atrial natriuretic hormone secretion: study in hyper- and hypothyroid patients

Abstract: Plasma atrial natriuretic hormone (ANH) values were evaluated in 28 hyperthyroid patients and in 11 hypothyroid patients and compared with 20 healthy subjects. In hyperthyroid patients plasma ANH basal levels were significantly (p<0.01) higher (14.2 \ m=+-\ 1.6 pmol/l) than in controls (7.8 \m=+-\0.4pmol/l) and in hypothyroid patients (6.4 \m=+-\0.3pmol/l). No significant differences were found between controls and hypothyroid patients. The propranolol-induced decrease in heart rate in hyperthyroid patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…After thyroid replacement these concentrations have increased in some reports (Kohno et al 1987, Zimmerman et al 1987, Woolf & Moult 1988, Rolandi et al 1992, Bernstein et al 1997 but not in others (Weissel et al 1986, Ladenson et al 1987. One of the possible explanations for these discrepancies may lie in the comparability of the groups, since in most studies the mean age of the hypothyroid patients is higher than that of the control group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…After thyroid replacement these concentrations have increased in some reports (Kohno et al 1987, Zimmerman et al 1987, Woolf & Moult 1988, Rolandi et al 1992, Bernstein et al 1997 but not in others (Weissel et al 1986, Ladenson et al 1987. One of the possible explanations for these discrepancies may lie in the comparability of the groups, since in most studies the mean age of the hypothyroid patients is higher than that of the control group.…”
Section: Discussionmentioning
confidence: 94%
“…In patients with hypothyroidism, plasma ANH concentrations have been reported to be low (Kohno et al 1987, Zimmerman et al 1987, Woolf & Moult 1988, Widecka et al 1990, Barna et al 1994, Ota et al 1994 or normal (Ladenson et al 1987, Rolandi et al 1992. After thyroid replacement these concentrations have increased in some reports (Kohno et al 1987, Zimmerman et al 1987, Woolf & Moult 1988, Rolandi et al 1992, Bernstein et al 1997 but not in others (Weissel et al 1986, Ladenson et al 1987.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of pertinent studies have shown that ANP levels in patients with untreated hyperthyroidism and hypothyroidism were significantly different from those of normal subjects 18,19,26,[28][29][30][31] and returned to normal after appropriate treatment. However, at least in one study different results were detected 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthemore, human studies revealed that plasma ANP levels are significantly higher in hyperthyroid and lower in hypothyroid patients compared to euthyroid controls (17)(18)(19)(20)(21) . ANP levels return to normal following appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have shown that plasma ANP secretion is affected by thyroid hormones, being higher in hyperthyroid patients compared to euthyroid controls [1012] and returning to normal levels after appropriate treatment [13]. There is a strong positive relationship between circulating thyroid hormones and both atrial and ventricular ANP mRNA contents [14, 15], supporting the hypothesis that ANP synthesis and/or secretion from atrial cardiomyocytes remain under thyroid hormone control.…”
Section: Introductionmentioning
confidence: 99%